Migration, cultural identity and diasporas: An identity economics approach - Aloys Prinz; Melissa Siegel (IZA Journal of Development and Migration, 2019)
Besides effects on economic well-being, migration of people with distant cultural backgrounds may also have large effects on people's cultural identity. In this paper, the identity economics of Akerlof and Kranton (2000) is applied to migration. Accordingly, it is assumed that the utility of both the immigrants and the native population encompasses economic well-being and cultural identity. The migration effect on cultural identity depends, among others, on the distance between cultures. In a simple immigration game it is shown that immigrants may prefer to live rather in diaspora communities than to integrate into the host countries' culture. This subgame-perfect equilibrium choice of immigrants seems the more likely the greater the cultural distance between their country of origin and the destination country is. Among the available policy instruments, restrictions on the freedom of movement and settlement of immigrants may be the most effective way to prevent the setup of large diaspora communities. For young immigrants and later generations of immigrants, integration via compulsory schooling is the most important policy. In general, cultural, religious and social institutions may support integration.
Keywords: D91; I31; J15; J61; 330; Akerlof-Kranton game; cultural identity; diaspora; economic well-being; identity economics; immigration